A Novel BN Polymorph in P4/mbm Phase with a (4, 4) Nanotube. Issue 1 (27th October 2021) - Zhao, Mo; Chen, Wei; Wu, Wei; Li, Bin
Abstract : Herein, based on density functional theory, a new boron nitride structure derived from diamond is designed, and its stability is also proved. The new boron nitride structure is denoted as P 4/ mbm BN. The elastic moduli (bulk modulus, shear modulus, and Young's modulus) of P 4/ mbm BN are slightly greater than those of C72 and T carbon, and the shear modulus and Young's modulus are larger than those of P ‐4 m 2 B7 N7, B11 N11, and B15 N15 . The shear modulus and Young's modulus of P 4/ mbm BN exhibit a smaller mechanical anisotropy than that of P ‐4 m 2 B7 N7, B11 N11, and B15 N15, where P ‐4 m 2 B15 N15 exhibits the greatest mechanical anisotropy of shear modulus and Young's modulus. The anisotropy of shear modulus in the (100), (010) plane of P ‐4 m 2 B15 N15 is 26.5 times that of P 4/ mbm BN, and the mechanical anisotropy of Young's modulus in (110) plane of P ‐4 m 2 B15 N15 is 35.6 times that of P 4/ mbm BN. P 4/ mbm BN is a wide and indirect bandgap semiconductor material with bandgap of 4.8 eV. Compared with silicon carbide and gallium nitride, P 4/ mbm BN has a wider bandgap, it might be more suitable for making high temperature, high frequency, radiation resistance, and high‐power devices. Abstract : The shear modulus and Young's modulus of the P 4/ mbm BN, proposed herein, are larger than those of P ‐4 m 2 B7 N7, B11 N11, and B15 N15 . Compared with SiC and GaN, P 4/ mbm BN has a wider bandgap of 4.8 eV, it might be more suitable for making high temperature, high frequency, radiation resistance, and high‐power devices.